Development of 3D rock fragmentation measurement system using photogrammetry - Jang, Hyong Doo; Topal, Erkan; Kitahara, I.; Kawamura, Y.; Endo, Y.; Degawa, R.; Mazara, Samson (TAYLOR & FRANCIS LTD, 2019)
Run-of-mine fragmentation is an important aspect of mine productivity optimisation, as it affects all mine-to-mill processes. In this study, a 3D rock fragmentation measurement (3DFM) system is proposed that can surmount the limitations of conventional 2D photo-based rock fragmentation measurement methods. To validate the proposed 3DFM performance, a laboratory-based comparison study was conducted using 100 randomly collected rock fragments. Conventional method exhibits relatively low and diffused results than the 3DFM. The proposed 3DFM can be considered as a new particle size distribution measurement method that should efficiently aid in improving mine productivity.